Indoor Thermal Environment of Various Semi-Enclosed Atrium Configurations of Institutional Building in Tropical Climate (International Journal of Built Environment and Sustainability, 2021)
The consideration of local climate is essential for the application of atrium in building. Different strategies and approaches in atrium configuration are required for different climates in ensuring its effectiveness.  Nevertheless, the final aim is still similar which is to provide a comfortable environment for the users. Hence, this study was executed to examine the effects of top and side configurations on the indoor thermal environment of semi-enclosed atrium in the tropical climate. The methodologies involved field measurement and questionnaire survey. The field measurements were executed at two different configurations of semi-enclosed atriums in the tropical climate of Malaysia. Meanwhile, the questionnaire surveys were executed simultaneously with the field measurements in obtaining the users’ thermal sensation and satisfaction. The findings indicated that the top configuration had more influence to the indoor thermal environment compared to the side configuration as it determined the amount of solar heat penetration into the atrium area. Meanwhile, the side configuration influenced the air velocity inside the atrium. The Faculty of Engineering and Built Environment’s atrium that has opaque top finishes was found to have the average indoor operative temperature of less than 30 °C throughout the day, though the average outdoor air temperature was more than 30 °C. It also had more hours with neutral thermal sensation felt by the users compared to the Faculty of Economics and Management’s atrium that has transparent materials for the top finishes. The study is useful in guiding the selection of appropriate strategy for an atrium in tropical climate
Keywords: Atrium; Configurations; Indoor thermal environment; Tropical climate